Secure Data Hiding in Audio-Video Steganalysis by Anti-Forensic Technique (International Journal of Engineering and Computer Science, 2017)
Steganography is used to encrypt any secret information like password, text and picture, audio behind original cover file. Original message is converted into cipher text by using mystery key and then hidden into the LSB of original image. The current work signifies cryptostegnography of audio and video which is the combination of image steganography, audio and video steganography by making use of Forensics Technique as a tool for authentication. The main aim is to hide secret data behind image and audio of video file. As video is the utilization of many still frames of images and audio, thus for hiding secret information any frames can be selected for audio and video. Suitable algorithm such as AES for security and authentication image processing is used, hence data security can be increased. And for data embedding, use 4LSB algorithm